Electrochemical effects after transarterial chemoembolization in combination with percutaneous irreversible electroporation: observations in an acute porcine liver model - Vollherbst, Dominik; Bertheau, Robert; Fritz, Stefan; Mogler, Carolin; Kauczor, Hans-Ulrich; Ryschich, Eduard; Radeleff, Boris; Sommer, Christof-Matthias (Journal of vascular and interventional radiology, 2016)
Purpose - To evaluate the effects of combined use of transarterial chemoembolization and irreversible electroporation (IRE) for focal tissue ablation in an acute porcine liver model. - Materials and Methods - Two established interventional techniques were combined: IRE with zones of irreversible and reversible electroporation and chemoembolization with microspheres, iodized oil, and doxorubicin. IRE was performed before chemoembolization in two pigs (pigs 1 and 2; IRE/chemoembolization group), chemoembolization was performed before IRE in two pigs (pigs 3 and 4; chemoembolization/IRE group), and only IRE was performed in two pigs (pigs 5 and 6). Five study groups were defined: IRE/chemoembolization (pigs 1 and 2), chemoembolization/IRE (pigs 3 and 4), IRE only (pigs 5 and 6), chemoembolization only (tissue outside the IRE zones in pigs 1-4), and control (untreated liver tissue outside the IRE zones in pigs 5 and 6). Animals were euthanized 2 hours after intervention. Size and shape of IRE zones on contrast-enhanced computed tomography, cell death on light microscopy, and doxorubicin tissue concentrations on chromatography and fluorescence microscopy were analyzed. - Results - Size and shape of IRE zones were not significantly different (eg, P = .067 for volume). A histologic marker for irreversible cell death was positive in IRE/chemoembolization, chemoembolization/IRE, and IRE groups only in the macroscopically visible IRE zones. Doxorubicin tissue concentrations were not significantly different (P = .873). However, in the reversible electroporation (RE) zones, broad areas with intense intranuclear doxorubicin accumulation were observed in IRE/chemoembolization but not in chemoembolization/IRE and chemoembolization groups. - Conclusions - IRE before chemoembolization enhances the intranuclear accumulation of doxorubicin in the RE zone.
Gesehen am 09.08.2019